Geographic variation in management of patients with placenta accreta spectrum: An international survey of experts (GPASS). Issue 1 (28th October 2021) - Brown, Alec D.; Hart, Jessica M.; Modest, Anna M.; Hess, Philip E.; Abbas, Ahmed M.; Nieto‐Calvache, Albaro J.; Bhide, Amarnath; Lim, Boon; Dunjin, Chen; Palacios‐Jaraquemada, José; Sentilhes, Loïc; Soma‐Pillay, Priya; et al.
Abstract: Objective: To describe global geographic variations in the diagnosis and management of placenta accreta spectrum (PAS). Methods: An international cross‐sectional study was conducted among PAS experts practicing at medical institutions in member states of the United Nations. Survey questions focused on diagnostic evaluation and management strategies for PAS. Results: A total of 134 centers participated. Participating centers represented each of the United Nations' designated regions. Of those, 118 (88%) reported practicing in a medium‐volume or high‐volume center. First‐trimester PAS screen was reported in 35 (26.1%) centers. Respondents consistently implement guideline‐supported care practices, including utilization of ultrasound as the primary diagnostic modality (134, 100%) and implementation of multidisciplinary care teams (115, 85.8%). Less than 10% of respondents reported routinely managing PAS without hysterectomy; these centers were predominantly located in Europe and Africa. Antepartum management and availability of mental health support for PAS patients varied widely. Conclusion: Worldwide, there is a strong adherence to PAS care guidelines; however, regional variations do exist. Comparing variations in care to outcomes will provide insight into the clinically significant practice variability. Abstract : This international study sought to determine the geographic variations in diagnosis and management of placenta accreta spectrum worldwide.